Surgical Treatment of Calcaneal Spur. - Eduardo Sarmiento Sánchez; Horacio Suárez Monzón; Rolando Delgado Figueredo; Juan Carlos Cabrera Suárez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: Pain in the plantar region of the heel is technically known as talalgia, and it is a very frequent complaint in the orthopaedic service in Guyana. Due to its frequent mortality, the current investigation was carried out. Objectives: To characterize the application of the surgical treatment to a group of patients in Guyana. Method: 70 patients surgically treated were studied presenting rebel talalgia with no responses to the conservative treatment. Age, sex, race, educational level, antibiotic prophylaxis, final outcomes, and patient's satisfaction with the treatment were the set of variables selected. Results: High morbidity of the heel pain syndrome was evidenced in this studied. The most frequent cause was the calcaneal spur. There is predominance in female Indian race. The high influenced of the socio-cultural factor in the genesis of this disease is proved as well as the impossibility of carrying out the conservative treatment due to high cost of medications. Conclusions: The efficacy achieved with combined treatment technique allowed the results obtained. All this contributed to achieve high satisfaction levels.